Taxonomic and nomenclatural notes on Philippine ferns. IV. Asplenium pahli (Polypodiales, Aspleniineae, Aspleniaceae), a new species from Leyte, Philippines - Salgado, Arthur Edward (Phytotaxa, 2021)
Asplenium pahli, a new species from Leyte, Philippines, is described. Morphological and distribution range differences between A. pahli, A. anisodontum, A. caudatum, A. falcatum, A. gueinzianum, and A. planicaule are discussed. The habitat and climate of Eastern Leyte is described.